Fullerenes and prospects of their use in foundry and metallurgical production - P. A. Vitiaz; N. A. Svidunovich; D. V. Kuis; Yu. A. Nikalaichyk; S. I. Rovin (Литьë и металлургия, 2021)
The article is devoted to a special nanostructured form of carbon – fullerenes; the discovery of which became one of the most important events in the field of physics in the 80s of the last century. The article discusses the issues of obtaining and using fullerenes and other nanostructured materials; including hybrid ones; in foundry and metallurgical production: for modifying casting alloys; binders and auxiliary molding materials; for obtaining ceramic and hybrid nanocomposites; and for other purposes. It also provides information on the creation and operation of the world’s leading research centers specializing in the synthesis and application of nanomaterials in metallurgy and foundry.